Assessing Health Risks Associated with Antibiotic Residues in Armenian Honey - Pipoyan, D. A.; Chirkova, V. I.; Beglaryan, M. R. (ՀԱԱՀ հիմնադրամ)
This study assessed potential risks associated with antibiotic residues in Armenian honey. Honey sample analysis revealed multiple antibiotics, in varying concentrations. Estimated daily intakes of antibiotics were calculated for different consumer clusters. The margin of exposure was determined based on acceptable daily intake values. The findings indicate that there are no risks to consumers regarding antibiotic residues in honey. However, it highlights the importance of controlling antibiotics in beekeeping practices to ensure honey safety.
Keywords: Food Science and Technology